Investigating the Impact and Effectiveness of an ICT-based Teaching Scenario on Secondary School Students’ Geospatial and Statistical Literacy: - Ourania Rizou; Aikaterini Klonari; Dimitris Kavroudakis (European Journal of Geography)
The case study investigates students’ statistical and geospatial literacy and their reaction to an ICT-based teaching scenario. The study involved 41 High School students’ in Lesvos Island, Greece. The intervention was applied in the ICT lab, in the context of a second-semester project on Geography. The means we employed to carry out students’ activities included worksheets and the web-based platform statistics4school. In order to check the effectiveness of this intervention, the sample completed assessment sheets and an anonymous self-reporting questionnaire. According to the results, students declared that they became more confident with statistical concepts and geospatial thinking. The same perspective was also reflected in their responses regarding developing cognitive and social skills and literacy in general. The intervention’s findings establish the basis according to which implementing new ICT-based teaching scenarios will support statistical, geospatial, and digital literacy.